Membrane Homeoviscous Adaptation in Sinorhizobium Submitted to a Stressful Thermal Cycle Contributes to the Maintenance of the Symbiotic Plant–Bacteria Interaction - Paulucci, Natalia Soledad; Cesari, Adriana Belén; Biasutti, María Alicia; Dardanelli, Marta Susana; Perillo, María Angélica (Frontiers in Microbiology, 2021)
Here, we estimated fast changes in the fluidity of Sinorhizobium meliloti membranes submitted to cyclic temperature changes (10ºC-40ºC-10ºC) by monitoring the fluorescence polarization (P) of DPH and TMA-DPH of whole-cell (WC) as well as in its outer (OM) and inner (IM) membranes. Additionally, the long-term response to thermal changes was demonstrated through the dynamics of the phospholipid and fatty acid composition in each membrane. This allowed the membrane homeoviscous adaptation by the return to optimal fluidity levels as measured by the PDPH/TMA-DPH in WC, OM, IM, and in multilamellar vesicles of lipids extracted from OM and IM. Due to probe partitioning preferences and membranes' compositional characteristics, DPH and TMA-DPH exhibited different behaviors in IM and OM. The rapid effect of cyclic temperature changes on the P was the opposite in both membranes, being the IM the one that exhibited the thermal behavior expected for lipid bilayers. Interestingly, only after the incubation at 40°C, cells were unable to recover the membranes pre-heating P levels when cooled up to 10°C. Solely in this condition, the formation of threads and nodular structures in Medicago sativa infected with S. meliloti were delayed, indicating that the symbiotic interaction was partially altered but not halted.